Childhood to Adult Neurodevelopment in Gene-Expanded Huntington’s Disease (ChANGE-HD): A prospective longitudinal neurodevelopmental study of Huntington’s disease - Mohit Neema; Nabil Halabi; Michael V. Freedberg; Peggy C. Nopoulos (PLoS ONE, 2026)
Although adult Huntington’s disease (HD) studies have significantly advanced our understanding of the course of degeneration, they may underrepresent critical neurodevelopmental aspects of the disease. Significant gaps remain in understanding how mutant huntingtin affects early neurodevelopment, its long-term impact, as well as potential implications for treatment outcomes. The Childhood to Adult Neurodevelopment in Gene-Expanded Huntington’s Disease ( ChANGE-HD; NCT01951588) study aims to evaluate brain structure and function in premanifest, at-risk children and young adults, and explore HD’s developmental origins. Here, we introduce the ChANGE-HD study, which will investigate and integrate the neurodevelopmental and neurodegenerative aspects of HD. The ChANGE-HD study is a prospective, seven-year multi-site observational study with an accelerated longitudinal design, where participants are not bound to a fixed schedule across multiple visits. Four hundred and fifty participants aged 6–30 years who are at risk for HD will be recruited and asked to return for multiple visits (if possible). At each visit, cognitive, motor, behavioral, blood/saliva, and MRI data are collected. Alongside ChANGE-HD, we are also recruiting individuals for the juvenile-onset HD (JOHD) study to investigate the neuropathology of this rarer form of HD. ChANGE-HD represents the first prospective multi-site study to systematically document brain structure and function during the premanifest phase of HD in children and young adults. Data collection is ongoing with first results anticipated in 2026–2027. The ChANGE-HD approach is likely to provide novel physiological insights and guide the development of therapeutic strategies tailored to both the developmental and degenerative phases of the disease.